Η Θρησκευτική Εκπαίδευση στο Λύκειο στην τομή της νεωτερικής και μετανεωτερικής σκέψης. Η λύση είναι η κονστρουκτιβιστική προσέγγιση; - Κουκουνάρας- Λιάγκης, Μ. (Επιστήμες Αγωγής, 2013)
This article provides the constructivist approach of religious education in Greek schools. As religious literacy is essential in interpretation of the contemporary world issues, religious education seems to be indispensable in schools according to international and European surveys and pedagogical theories. However, E.U. recommends a compulsory religious education provided to be objective and non-confessional, as it is in Greece according to the two recent curriculums of 2003 and 2011. The author imposes constructivist approach of religious education because it meets the attainments of the education generally and especially a post modern religious education. He also suggests a stage pedagogical strategy of the instruction, posing a particular proposal for the forthcoming change of religious education in the 4th, 5th and 6th years of High School (Lyceum).